Propuesta de ampliación y complementación, de los servicios, para el hospital San Roque de Pradera, Valle. (2022)
This degree work project proposes the expansion and complementation of the services currently provided by the San Roque hospital in the municipality of Pradera, Valle del Cauca, which manages to cover the entire population of the municipality as well as th e surrounding municipalities, with spaces spacious that provide comfort and good care to patients.